2020
DOI: 10.20944/preprints202008.0236.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impacts of The Invasive Seaweed <em>Asparagopsis armata</em> Exudate on Rockpool Invertebrates

Abstract: The marine red algae Asparagopsis armata is an invasive species which competitive advantage arises from the production and release of large amounts of toxic compounds to the surrounding invaded area, reducing the abundance of native species. The main objective of this study was to evaluate the effects of this invasive seaweed on marine invertebrates by exposing the common prawn Palaemon elegans and the marine snail Gibbula umbilicalis to the exudate of this macroalgae. The seaweed was collected and placed in t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 34 publications
(22 reference statements)
2
3
0
Order By: Relevance
“…Although we did not measure some peroxisomal enzymes (such as CAT) in the muscle tissue, a correlation between lipids metabolism and peroxisomal enzyme activities has been previously described [71]. On the other hand, and in agreement with our results, an increase in lipid content of G. umbilicalis exposed to A. armata exudate was observed and related with a concomitant decrease in feeding activity, leading to less energy expenditure [17]. On the other hand, the enzymatic activity of LDH, that plays an important role in the anaerobic pathway of energy production and is responsible for the reduction of pyruvate to lactate in glycolysis [72], was not altered.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Although we did not measure some peroxisomal enzymes (such as CAT) in the muscle tissue, a correlation between lipids metabolism and peroxisomal enzyme activities has been previously described [71]. On the other hand, and in agreement with our results, an increase in lipid content of G. umbilicalis exposed to A. armata exudate was observed and related with a concomitant decrease in feeding activity, leading to less energy expenditure [17]. On the other hand, the enzymatic activity of LDH, that plays an important role in the anaerobic pathway of energy production and is responsible for the reduction of pyruvate to lactate in glycolysis [72], was not altered.…”
Section: Discussionsupporting
confidence: 91%
“…Mussels' survival decreased to 50% when exposed to only about 3.67% of exudate. Similar 96h-LC50 values were reported by Silva et al [17] for the gastropod G. umbilicalis (2.79%) and the prawn P. elegans (5.04%). Another study comparing the communities of peracarid species inhabiting A. armata and Corallina elongata, a red macroalga native from the Atlantic coast and abundant in the subtidal zone of Azores [67], showed that even though A. armata hosts a diversity of crustacean assemblages [6], its presence might lead to an impoverishment of epifaunal peracarid.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Asparagopsis armata produces very high amounts of secondary metabolites including volatile components as phenolic compounds [24], which toxicity to invertebrates, and seaweeds has often been associated to the invasive process [25,26]. These phenolic compounds from seaweeds have also shown to vary throughout the year [27], while the release of defensive compounds may also be altered by several abiotic factors such as temperature, light, and nutrient availability [28].…”
Section: Assemblage Compositionmentioning
confidence: 99%
“…Due to their nature, grazers play an important role in structuring macroalgal assemblages, but secondary metabolites (terpenes, phenolic compounds, etc.) of A. armata ought to affect the palatability, or acceptability to herbivores [25,26]. Many of the gastropod species are microherbivores that feed on the biofilm established on the macrophyte fronds.…”
Section: Assemblage Compositionmentioning
confidence: 99%